2018
DOI: 10.1155/2018/7015272
|View full text |Cite
|
Sign up to set email alerts
|

Use of Expectation Disconfirmation Theory to Test Patient Satisfaction with Asynchronous Telemedicine for Diabetic Retinopathy Detection

Abstract: Objective The purpose of the study is to extend research on patient satisfaction with telemedicine services by employing the theoretical framework of Expectation Disconfirmation Theory (EDT) for diabetic retinopathy screenings focusing on rural patients. Method Adult subjects (n=220) with diabetes were recruited from a single family practice office in rural Iowa. Subjects completed a “pre” survey concerning their forward-looking perceptions of telemedicine prior to using telemedicine for detection of diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 104 publications
1
29
0
Order By: Relevance
“…A plausible implication is that investigators should explicitly account for participants' prior beliefs in the context of N-of-1 experiments and, indeed, use them in constructing posterior probabilities that are returned to patients. Another possible explanation, drawing on expectation disconfirmation theory (41), is that participants who were pleasantly surprised by a positive result (despite expecting a negative outcome) were more likely to be enthused about the activity going forward.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible implication is that investigators should explicitly account for participants' prior beliefs in the context of N-of-1 experiments and, indeed, use them in constructing posterior probabilities that are returned to patients. Another possible explanation, drawing on expectation disconfirmation theory (41), is that participants who were pleasantly surprised by a positive result (despite expecting a negative outcome) were more likely to be enthused about the activity going forward.…”
Section: Discussionmentioning
confidence: 99%
“…This way, LoG filters together with Matched Filter are utilized to identify the transient bright lesions and the Gaussian intensity-like dark lesions. The 2-dimensional MF and LoG prototype kernel mathematical expressions are given respectively via equation 2and (3).…”
Section: ) Gaussian Filtering Matched Filters and Laplaciansmentioning
confidence: 99%
“…the retinopathy can only be slower during the early stages of the disease [3]. The identification by repeated examination of patients affected of these initial lesions (mainly Microaneurysms and small blood cells) is expected as a new possibility of improving retinopathy treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted on diabetic patients, telemedicine screening was found to be a valid screening method, and most people wanted to use this method in subsequent experiments [50][51][52]. Studies in remote surveillance centers have shown that a remote medical screening program is a safe and efficient device for the diagnosis and treatment of diabetic retinopathy.…”
Section: Telemedicinementioning
confidence: 99%
“…Studies in remote surveillance centers have shown that a remote medical screening program is a safe and efficient device for the diagnosis and treatment of diabetic retinopathy. Data suggest that diabetic diagnostic retinopathy screening program can be prevented to prevent blindness in diabetic patients, and the integration of telemedicine and screening is a collaborative effort between primary care physicians and ophthalmologists in timely and effective screening and treatment [50,53].…”
Section: Telemedicinementioning
confidence: 99%